2021
DOI: 10.1038/s41418-021-00811-1
|View full text |Cite|
|
Sign up to set email alerts
|

MLKL promotes cellular differentiation in myeloid leukemia by facilitating the release of G-CSF

Abstract: The blockade of cellular differentiation represents a hallmark of acute myeloid leukemia (AML), which is largely attributed to the dysfunction of lineage-specific transcription factors controlling cellular differentiation. However, alternative mechanisms of cellular differentiation programs in AML remain largely unexplored. Here we report that mixed lineage kinase domain-like protein (MLKL) contributes to the cellular differentiation of transformed hematopoietic progenitor cells in AML. Using gene-targeted mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Inhibition of RIPK3 attenuated cardiac ischemia‒reperfusion injury [ 58 ] and sepsis [ 59 ] by reducing mitochondrial dysfunction, and inhibition of the RIPK1-RIPK3 pathway reduced tumor cell metastasis by decreasing vascular endothelial permeability [ 60 ]. Furthermore, MLKL attenuated colon inflammation and colitis tumorigenesis via suppression of inflammatory responses [ 17 ], inhibited intestinal tumorigenesis by suppressing the IL-6/JAK2/STAT3 pathway [ 61 ] and promoted cellular differentiation in myeloid leukemia by facilitating the release of G-CSF [ 18 ]. Inhibition of MLKL prevented obesity-induced insulin resistance in mice [ 20 ] and promoted intracellular Listeria replication [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of RIPK3 attenuated cardiac ischemia‒reperfusion injury [ 58 ] and sepsis [ 59 ] by reducing mitochondrial dysfunction, and inhibition of the RIPK1-RIPK3 pathway reduced tumor cell metastasis by decreasing vascular endothelial permeability [ 60 ]. Furthermore, MLKL attenuated colon inflammation and colitis tumorigenesis via suppression of inflammatory responses [ 17 ], inhibited intestinal tumorigenesis by suppressing the IL-6/JAK2/STAT3 pathway [ 61 ] and promoted cellular differentiation in myeloid leukemia by facilitating the release of G-CSF [ 18 ]. Inhibition of MLKL prevented obesity-induced insulin resistance in mice [ 20 ] and promoted intracellular Listeria replication [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Nagy et al found that Ripk3 -/- mice were not protected from high-fat diet (HFD)-induced liver injury, whereas knockout of Mlkl exerted a protective effect [ 10 , 11 ], which suggested that the molecular machinery in the necroptotic pathway is complex and varies among diseases. In addition, multiple noncanonical mechanisms for RIPK3 and MLKL have been identified [ 12 20 ], some of which were even independent of inflammation and necroptosis [ 15 , 17 , 18 , 20 ]. The activation of RIPK3 [ 21 25 ] and MLKL [ 25 , 26 ] signaling were also involved in the pathogenesis of AP; however, their contribution to disease severity remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cancer stem cells represent a subpopulation of cancer cells capable of self-renewal, tumor initiation, and therapeutic resistance [ 5 ]. In our previous study, we reported that the cancer stem cell population is highly resistant to chemotherapy due to its quiescence behavior [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumors are composed of different types of cells with different genetic, epigenetic and phenotypic background / properties, which can make them respond differently to different treatments [ 3 , 4 ]. Cancer stem cells (CSCs) are a subpopulation of tumor cells that possess stem cell-like properties and are responsible for tumor initiation, maintenance, and resistance to therapy [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…3) Remodeling microenvironment secretome, which not only promotes host immune tolerance but also might enhance tumor stemness / proliferation (e.g., regulating granulocyte colony-stimulating factor, IL-10, and IL-6, etc.) [7,8]. 4) Recruiting immunosuppressive cells in the microenvironment (e.g., myeloid-derived suppressor cells, regulatory T cells, etc.)…”
Section: Introductionmentioning
confidence: 99%